Luminescent graphene quantum dots fabricated by pulsed laser synthesis - Habiba, Khaled; Makarov, Vladimir I.; Avalos, Javier; Guinel, Maxime J.F.; Weiner, Brad R.; Morell, Gerardo (Carbon (New York), 2013)
Graphene has been the subject of intense research in recent years due to its unique electrical, optical and mechanical properties. Furthermore, it is expected that quantum dots of graphene would make their way into devices due to their structure and composition which unify graphene and quantum dots properties. Graphene quantum dots (GQDs) are planar nano flakes with a few atomic layers thick and with a higher surface-to-volume ratio than spherical carbon dots (CDs) of the same size. We have developed a pulsed laser synthesis (PLS) method for the synthesis of GQDs that are soluble in water, measure 2–6nm across, and are about 1–3 layers thick. They show strong intrinsic fluorescence in the visible region. The source of fluorescence can be attributed to various factors, such as: quantum confinement, zigzag edge structure, and surface defects. Confocal microscopy images of bacteria exposed to GQDs show their suitability as biomarkers and nano-probes in high contrast bioimaging.